Early life lead exposure causes gender-specific changes in the DNA methylation profile of DNA extracted from dried blood spots. (June 2015) - Sen, Arko; Heredia, Nicole; Senut, Marie-Claude; Hess, Matthew; Land, Susan; Qu, Wen; Hollacher, Kurt; Dereski, Mary O; Ruden, Douglas M
Aims: In this paper, we tested the hypothesis that early life lead (Pb) exposure associated DNA methylation (5 mC) changes are dependent on the sex of the child and can serve as biomarkers for Pb exposure.Methods: In this pilot study, we measured the 5mC profiles of DNA extracted from dried blood spots (DBS) in a cohort of 43 children (25 males and 18 females; ages from 3 months to 5 years) from Detroit.Result & Discussion: We found that the effect of Pb-exposure on the 5-mC profiles can be separated into three subtypes: affected methylation loci which are conserved irrespective of the sex of the child (conserved); affected methylation loci unique to males (male-specific); and affected methylation loci unique to females (female-specific).